Research of hydraulic streams in cooling case of crystallizer of continuous circular casting by frosting - E. I. Marukovich; V. F, Bevza; V. Ju. Stetsenko (Литьë и металлургия, 2003)
For continuous circular casting by frosting by method of physical modelling there have been investigated on the transparent model the hydrodynamic flows of cooling water in crystallizer.